Pengembangan Gaya Kepemimpinan Kepala Sekolah terhadap Kinerja Guru di SMP Negeri 1 Afulu - Anariati Nazara; Ferdiaman Zalukhu; Hepi Friska Mendrofa; Arozatulo Bawamenewi (Journal on Education, 2023)
This study uses a qualitative approach. inj approach is used to gain in-depth understanding of. how much influence does the school principal's leadership have on the performance of afulu 1 public junior high school teachers. Qualitative research enables researchers to explore and understand complex and contextual phenomena through the collection and analysis of data across multiple texts and narratives. from the results of interviews that have been obtained by research at afulu 1 public junior high school, it can be concluded that a leader applies an informative leadership style in improving teacher performance.